User's profile of a portuguese thermal establishment: empirical study - Vaz, Márcia (2022)
The thermal tradition plays an important role for society by naturally promoting and improving individuals' wellbeing. Thermal treatments help cure diseases and prevent pathologies, including mental and social ones, providing users with a better quality of life. At the same time, such a wellness activity introduces leisure components resulting from a more holistic perspective on health and well-being. Given the importance of this topic, which just recently started to be the object of empirical studies in Portugal, the present study aims to identify the profile of those who attend a thermal spa. For this purpose, a self-administrated questionnaire was applied to the Termas de Chaves' users during the 2021 thermal season, i.e., between August and November. A convenience method of non-probability sampling allowed to obtain a sample of 220 thermal users. This establishment, located in the sub-region of Alto Tâmega, North of Portugal, has 300 years of history and vast experience in providing thermal services for different audiences. To better understand and identify the features of the thermal spa user, sociodemographic data were analysed and identified the characteristics, motivations, behaviours, preferences, and perceptions of the thermal spa users under study. The data collected was submitted to treatment through an exploratory quantitative analysis. The distribution data analysis was elaborated using frequencies, centrality and variability descriptive measures complemented by TwoStep cluster analysis. The results showed that most of the participants in Chaves thermal spa are women, with an average age of 69 years (SD=12.556), married, retired, and living in the northern region of Portugal. They seek these services in the season between summer and autumn, for medical advice, mainly for therapeutic reasons, and stay in the thermal spa, on average, for 14 days (SD=2.667). Moreover, the cluster analysis identifies three different groups of users to which thermal stakeholders should consider different policy approaches. By defining the users' profile, this empirical research presents a practical contribution since it provides a strategic orientation for the thermal establishments' stakeholders aiming, essentially, at the (re)qualification of supply and the increase of demand, thus contributing to the sectoral and regional competitiveness.